Rosetta Stone for Cancer Cure: Comparison of the Anticancer Capacity of Endogenous Estrogens, Synthetic Estrogens and Antiestrogens - Zsuzsanna Suba (Frontiers Media S.A., 2023)
This work presents the history of the recognition of principal regulatory capacities of estrogen hormones having been mistakenly regarded as breast cancer promoting agents for more than 120 years. Comprehensive analysis of the results of clinical, epidemiological, immunological and molecular studies justified that endogenous estrogens are the principal regulators of embryonic development, survival and reproduction via orchestrating appropriate expression and even edition of all genes in mammalians. Medical use of chemically modified synthetic estrogens caused toxic complications; thromboembolic events and increased cancer risk in female organs as they proved to be endocrine disruptors deregulating estrogen receptors (ERs) rather than their activators. Synthetic estrogen treatment exhibits ambiguous correlations with cancer risk at different sites, which may be attributed to an inhibition of the unliganded activation of estrogen receptors (ERs) coupled with compensatory liganded activation. The principle of estrogen induced breast cancer led to the introduction of antiestrogen therapies against this tumor; inhibition of the liganded activation of estrogen receptors and aromatase enzyme activity. The initial enthusiasm turned into disappointment as the majority of breast cancers proved to be primarily resistant to antiestrogens. In addition, nearly all patients showing earlier good tumor responses to endocrine therapy, later experienced secondary resistance leading to metastatic disease and fatal outcome. Studying the molecular events in tumors responsive and unresponsive to antiestrogen therapy, it was illuminated that a complete inhibition of liganded ER activation stimulates the growth of cancers, while a successful compensatory upregulation of estrogen signal may achieve DNA restoration, tumor regression and patient's survival. Recognition of the principal role of endogenous estrogens in gene expression, gene edition and DNA repair, estrogen treatment and stimulation of ER expression in patients may bring about a great turn in medical practice.